Construction of Neonatal PICC Nursing Quality Evaluation System - Shi Xiaoli; Hao Weiyan; Dandan Li (Applied Bionics and Biomechanics)
Objective. In order to improve the quality of neonatal care, this study analyzed the construction of PICC and scientifically evaluated the quality of PICC. Methods. A total of 100 neonatal patients admitted to the Pediatric Medical Intensive Care Unit of the People’s Hospital in Laizhou City of Shandong Province between January 2015 and December 2018 were selected for nursing intervention. They were randomly divided into 50 cases in the observation group and 50 cases in the reference group. In the observation group, 50 were neonatal patients who received and completed PICC catheterization care, and in the reference group, 50 were neonatal patients with traditional conventional puncture care, PICC nursing quality evaluation index system, and nursing quality standard were applied, and questionnaire survey and patient satisfaction survey were conducted in the treatment. The two groups were compared for the success rate of one puncture, catheter detachment, treatment of local bleeding, incidence of nursing risk during other treatment, and other related nursing quality results. Results. The incidence of related medical and nursing risks in neonatal patients such as one-time puncture success rate, catheter detachment during treatment, and local bleeding was significantly lower than those in neonatal patients receiving conventional nursing methods. The incidence of nursing risk events during puncture was effectively reduced. It is shown in the comparison of adverse events in neonatal pediatric nursing in the fourth quarter of 2017 and 2018. In 2018, the proportion of adverse events in neonatal nursing is decreasing, the quality index of nursing is improving, and the satisfaction of patients’ families and relevant personnel in treatment is increasing. Conclusion. The construction and application of neonatal PICC nursing quality evaluation system can improve the success rate of one-time puncture, reduce the pain of newborns, improve the nursing quality evaluation system, scientifically and reasonably provide effective methods and basis for hospital PICC nursing, and play an important role in the development of pediatric nursing.